Biological Therapy, Therapeutic Approaches and Future Perspectives in the Treatment of Chronic Rhinitis - Agata Magierska; Zuzanna Szczepaniak; Olga Ptak; Krzysztof Gomułka (Nicolaus Copernicus University in Toruń, 2024)
Introduction: The widespread prevalence of chronic rhinitis necessitates the search for effective treatment methods. Modern type of medicine is biological treatment. Pathomechanism of AR is based on lymphocytes Th-2 reaction and connected with that cascade of effects. Biological treatment in the form of monoclonal antibodies blocks interleukins or immunoglobulin E signaling and leads to decrease in inflammatory reaction. Mechanism of action of these drugs and short period of use in AR requires patients to meet the including criteria and is usually used after other treatment options have run out. Taking under consideration the amount of patients suffering from AR and the impact on the quality of life indicates that there is still a need for new drugs and  using drugs which are useful in similar diseases.  Purpose of the work: This study aims to review and evaluate biological drugs used or having the potential to be used in the treatment of allergic rhinitis (AR), including: omalizumab, dupilumab, mepolizumab, reslizumab and the possibility of their use on a wider scale in the future. Materials and methods: An analysis of research papers available on PubMed and Google Scholar was undertaken using the following keywords: chronic rhinitis with nasal polyps; immunotherapy; monoclonal antibodies; allergic rhinitis; Quality of Life in rhinitis; omalizumab; dupilumab; mepolizumab; reslizumab; biological treatment during pregnancy; Results: The use of biological drugs in AR results in a significant improvement in symptom control and an increase in quality of life. This option can be an effective form of treatment for nasal polyps, reducing the risk of needing sinus surgery. However, the criteria for using these drugs are still very limiting, due to the lack of specific biomarkers that could early indicate a high chance of success. Biological drugs seem to be a great opportunity and a worthwhile possibility in the treatment of people with chronic allergic rhinitis.